EFFECT OF ZINC FERTILIZATION ON GROWTH, YIELD AND QUALITY OF WHEAT GROWN UNDER AGRO-CLIMATIC CONDITION OF KYMORE PLATEAU OF MADHYA PRADESH, INDIA - K. S. KERAM,; B. L. SHARMA,; M. L. KEWAT,; G. D. SHARMA, (The Bioscan, 2014)
Field experiments was conducted under All India Co-ordinated Research Project on “Micro, secondary nutrients and pollutant elements in soils and plants” during two consecutive years 2010-11 and 2011-12 with fallowwheat cropping sequence at the Research Farm of Department of Soil Science and Agricultural Chemistry, J.N. Krishi Vishwa Vidyalaya, Jabalpur (M.P.) to study the response of Zn application on growth, yield attributes, yield and quality of wheat in a Zn deficient soil (Vertisol). The recommended dose of N, P and K was applied @ 120 N: 60 P2O5: 40 K2O kg ha-1 in combination with Zn @ 0, 1.25, 2.5, 5, 10 and 20 kg ha-1 as zinc sulphate. The results revealed that the application of increasing levels of Zn @ 5, 10 and 20 kg ha-1 significantly increased the growth parameters viz., plant height, plant population, number of leaves per plant, dry weight per plant and leaf area index, yield attributing characters like length of earhead, number of grains per ear head, number of effective tillers per meter and 1000-grain weight, grain and straw yields as well as harvest index with the increasing levels of Zn at different growth stages as compared to NPK fertilization alone. Further, the quality parameters like protein (crude and true) in wheat grain were markedly increased by the application of increasing levels of Zn as compared to NPK alone. Thus, the present studies indicated that the application of 10 kg Zn ha-1 with 100 % NPK on wheat crop enhanced the productivity as well as maintained the quality of wheat grain.